(untitled) (International journal of artificial intelligence, 2026)
This article analyzes the pedagogical mechanisms of forming a civic culture in students. Civic culture is an important socio-psychological quality that reflects a person's active participation in public life, respect for the law , a sense of social responsibility, and understanding of democratic values. The study scientifically and theoretically analyzes the pedagogical conditions, educational technologies, and educational mechanisms for forming a civic culture in the educational process.